Derivation of the clinical grade human embryonic stem cell line RCe020-a (RC-16) - P.A. De Sousa; B.J. Tye; K. Bruce; P. Dand; G. Russell; D.M. Collins; A. Greenshields; K. McDonald; H. Bradburn; A. Laurie; J.M. Downie; M. Bateman; et al. (Stem Cell Research, 2016)
The human embryonic stem cell line RCe020-A (RC-16) was derived under quality assured compliance with UK regulation, European Union Directives and International guidance for tissue procurement, processing and storage according to Good Manufacturing Practice (GMP) standards. The cell line was derived from a failed to fertilise oocyte voluntarily donated as unsuitable or surplus to fertility requirements following informed consent. RCe020-A (RC-16) shows normal pluripotency marker expression and differentiates to mesoderm and potentially ectoderm in vitro. It has an abnormal 47XX, +14, i(20)(q10) female karyotype and microsatellite PCR identity, HLA and blood group typing data is available.